The pre- and post-COVID-19 pandemic dengue fever patterns in southeastern coastal China in 2019 and 2024: molecular evolution and strain replacement - Zhang, Tianran; Shi, Yaqi; Zhang, Leyi; Wang, Jian; Yu, Chengchao; Lv, Binbin; Wu, Sisi; Huang, Yiru; Liu, Xuewei; Dai, Hupiao; Zhou, Mingshi; Liao, Yanjuan; et al. (Frontiers in Microbiology, 2025)
BackgroundThe evolutionary dynamics of dengue virus type 1 (DENV-1) in non-endemic settings such as southeastern coastal China where outbreaks predominantly stem from imported cases, remains insufficiently defined, particularly in relation to lineage displacement dynamics.MethodsNinety-three DENV-1 isolates (56 from 2019, 37 from 2024) collected in southeastern coastal China underwent whole-genome sequencing. Phylogenetic relationships were inferred using maximum likelihood methods under the GTR + G + I model. Selection pressures were assessed through FEL, MEME, SLAC, and FUBAR. Recombination was analyzed using seven detection algorithms implemented in RDP4. Hamming distances were used to profile amino acid substitutions. Epitope mapping was performed by comparative alignment against CYD-TDV and TAK-003 vaccine reference strains.ResultsPhylogenetic inference placed all isolates within genotype I, yet 2019 and 2024 sequences segregated into distinct clades: 1I_E.1 and 1I_K.2, respectively. Codon-level analyses consistently indicated purifying selection. Eighteen recombination events were identified, predominantly involving strains of Vietnamese and Cambodian origin. A total of 40 non-synonymous substitutions were conserved across both periods, while 24 mutations were exclusive to 2024 isolates, with marked enrichment in NS3 and NS5 proteins. Epitope analyses revealed 9 and 17 antigenic variants within neutralizing domains of CYD-TDV and TAK-003, respectively.ConclusionComplete genotype turnover of DENV-1 occurred in southeastern coastal China between 2019 and 2024, driven by displacement of lineage 1I_E.1 by 1I_K.2, with implications for local transmission patterns. Observed antigenic divergence between temporal isolates emphasizes the importance of sustained genomic monitoring and targeted intervention strategies tailored to circulating strains in this region.